Studi Meta-Analisis: Small Effect Size pada Korelasi Antara Proactive Personality dan Job Performance - Aisyah, Farras Fajrina; Yudiarso, Ananta (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2023)
Job performance has an important role in organizational development because along with the times and significant changes in the world of work, job performance must adapt and develop rapidly. Various types of research on job performance have been carried out by several researchers, one of which is linking job performance with aspects of personality. One of the personal aspects used in this study is Proactive personality. Proactive personality is considered important by most people in improving one's work performance. This was revealed because proactive personality is a personality where there is personal initiative to change the environment. Employees with proactive personality also have the willingness to take a self-initiative role when they have to contribute and identify the various situations and activities they face. In searching for this study, a number of studies have shown inconsistent results between the relationship between proactive personality and job performance. Therefore, this meta-analysis study will answer the correlation between proactive personality and job performance. From screening results of the journals to be analyzed, it was found that 5 journals were selected according to the criteria that met the inclusion criteria. Based on data from 5 journals that met the inclusion criteria, an effect size value was found of 0.216 (95% CI = 0.065 to 0.367), p = 0.005, with an inconsistency value (I2) of 91.23%. from these results it can be said that proactive personality on job performance in this study is included in the category that has a small effect on its influence.